Association between the ratio of aspartate aminotransferase to alanine aminotransferase and risk of diabetes and the mediating effect of BMI: a comparative analysis in Chinese and Japanese populations - Gu, Mengyao; Niu, Nan; Liao, Yuheng; Hu, Haofei; Gu, Dayong (Frontiers in Endocrinology, 2026)
ObjectiveDespite the AST/ALT ratio emerging as a promising diabetes predictor, current research lacks comprehensive understanding of population-specific patterns and underlying mechanisms. This study aims to investigate the AST/ALT-diabetes risk relationship in Chinese and Japanese populations, specifically examining non-linear relationships, population-specific thresholds, and BMI’s potential mediating role to address existing knowledge gaps.MethodsWe performed a retrospective cohort analysis using data from the China Rich Healthcare Group (n=84,281) and Japanese NAGALA database (n=15,291). AST/ALT ratio was calculated by dividing AST concentration by ALT concentration. Diabetes was defined by fasting plasma glucose ≥7.00mmol/L or self-reported diagnosis. We employed Cox proportional hazards models, including restricted cubic splines to explore non-linear relationships, two-piecewise regression for identifying population-specific thresholds, and mediation analysis to quantify BMI’s mediating effect on the AST/ALT-diabetes risk association.ResultsIn a cohort of 99,572 participants with 1,403 new diabetes cases, AST/ALT showed a significant negative association with diabetes risk across Chinese and Japanese populations (HR per unit increase: Chinese: 0.417, 95% CI: 0.341-0.510; Japanese: 0.631, 95% CI: 0.416-0.956). Country-specific variations were evident, with distinct non-linear relationships: Chinese participants exhibited risk reduction until AST/ALT reached 0.912, while Japanese participants showed an inflection point at 0.882. BMI’s mediating effect differed markedly between populations, with a higher proportion in Japanese participants (32.22%), suggesting nuanced pathophysiological mechanisms underlying the AST/ALT-diabetes relationship.ConclusionsOur study unveils significant ethnic variations in the AST/ALT-diabetes interaction, highlighting population-specific diagnostic thresholds and mediation mechanisms. These insights advocate for customized screening approaches and suggest that AST/ALT and BMI-targeted interventions may yield differential outcomes across East Asian populations, emphasizing the critical need for precision-based medical strategies.